TELECOMMUNICATIONS AND THE FUNDAMENTAL RIGHT TO HEALTH PROTECTION - Alex David Morales Acosta; Sergio Antonio Sánchez Hernández; Héctor Urzola Berrio; Julio Álvarez Month; Nadin Madera Arias (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The emission levels and the impact that electromagnetic fields have worry governments around the world. In 2011, the Council of Europe warned about the effects of these. The International Telecommunication Union – ITU-T established recommendations that contain essential elements for the deployment of infrastructure. In Colombia, Law 1751 of 2015 addresses issues such as exposure limits, public and environmental health, and risk management. Therefore, the objective of this article is to describe a real picture of whether the capabilities and functions of telebases affect the fundamental right to health protection. To do this, a descriptive methodology was used, reviewing academic, scientific and legal documents. The results show that, despite the considerations, there is no clear evidence that guarantees that there is a real risk to the health of people who are near the telebases. Although the conclusion is reached that health is a fundamental right and should be considered above other types of rights such as digital inclusion.